El lèxic botànic en el Libre de Caça i els termes corresponents en altres tractats romànics. - I MIRALLES, ANTONI MAS (Scripta)
In the Middle Ages, the falconry treaties focused on, among other topics, describing the symptoms and diseases of the birds, and offered as pallative care different therapeutic remedies from medicinal plants. This article presents a list of botanical terms used in five Medieval falconry works in five Romance languages: Portuguese, Spanish, Catalan, French and Italian. From the Latin scientific term, consisting of the genus and species, we propose its etymology together with the current term. Finally, we present a posible classification and distribution by words and languages.